World Investment and Political Risk 2011 - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2013)
The mission of the Multilateral Investment Guarantee Agency (MIGA) is to promote foreign direct investment (FDI) into developing countries to support economic growth, reduce poverty, and improve people's lives. As part of this mandate, the agency seeks to foster a better understanding of investors' perceptions of political risk as they relate to FDI, as well as the role of the political risk insurance (PRI) industry in mitigating these risks. Today's economic turbulence and fragility in developed countries are again posing challenges for the global economy. Developing countries are feeling the impact through multiple channels, including through the flows of FDI and private capital. Having rebounded sharply in 2010, FDI flows to developing countries continued to increase in 2011, but are expected to moderate going forward. The report highlights once again the salience of political risk as an important concern for multinational enterprises that seek to invest in developing countries. This is also reflected in the increased issuance of new political risk insurance in 2010, a trend that seems to be continuing in 2011, helped by a growing awareness of insurance as a risk-mitigation tool. This year the report also pays special attention to the FDI picture in the Middle East and North Africa region in light of the Arab Spring, as well as the reaction of multinational enterprises to these developments. This year's report puts a spotlight on expropriation, a political risk with a long and recurring history, and examines motivations of host-country governments in deciding whether to expropriate. The report also highlights the role of political or economic shocks in triggering expropriations. It finds that investor disputes are more likely to be resolved by democratically elected governments rather than non-democratic regimes. This suggests that the propensity to expropriate is significantly higher in countries with non-democratic regimes, a finding that should be of interest to investors who are more concerned about political stability than about regime type and political institutions. Research conducted for this report, including the MIGA- Economist Intelligence Unit (EIU) survey and discussions with London-based private sector PRI underwriters and brokers, showed that the views of investors and PRI providers regarding regime type and expropriation risk differ slightly. Underwriters and brokers did not find the empirical results surprising and agreed that these results support their overall underwriting views.